A passenger movement forecast and optimisation system for airport terminals. (1st January 2011) - Richter, Stefan; Voß, Stefan; Wulf, Julian
This paper describes a system to forecast and optimise movements of the passengers inside airport terminal buildings. Three key technologies and their interactions are considered: firstly, the classification of passengers into different groups is described; secondly, the actual path-finding based on graph-theoretical methods is explained; thirdly, methods are introduced to reflect the spatial utilisation of the terminal floor space in the model. Each methodology is specifically selected to solve the designated problem in the best possible way. The main finding of this paper is the illustration of the interaction of these three different methodologies and how it can assist in passenger-handling processes on ground.